Photodegradation of copolyester films: A mechanistic study. Issue 10 (16th October 2018) - Arangdad, Kiarash; Detwiler, Andrew; Cleven, Curtis D.; Burk, Christopher; Shamey, Renzo; Pasquinelli, Melissa A.; Freeman, Harold; El‐Shafei, Ahmed
ABSTRACT: The photodegradation of copolyesters based on 1, 4‐cyclohexanedimethanol (CHDM), tetramethyl‐1, 3‐cyclobutanediol, and terephthalic acid units was investigated using various analytical methods. Photodegradation products were characterized using Fourier transform infrared (FTIR), liquid chromatography–mass spectrometry (LC–MS), and X‐ray Photoelectron spectroscopy (XPS) analysis. The homolytic scission of C‐O bonds of ester groups through a Norrish Type I reaction was supported by time of flight secondary ion mass spectrometry and LC–MS results, while nuclear magnetic resonance analysis confirmed hydrogen abstraction from the tertiary carbon of CHDM units in the trans ( equatorial‐equatorial ) conformation. Chain scission through Norrish Type II reaction is also responsible for the formation of carboxylic acid end group. Fluorescence emission from irradiated glycol modified poly(ethylene terephthalate) films demonstrated the formation of mono‐ and dihydroxyterephthalate species. Furthermore, FTIR and XPS valence band analysis confirmed configurational changes, in the polymer chain due to photodegradation. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47148. Abstract : Photodegradation of Copolyesters.